2017
DOI: 10.1371/journal.pone.0170490
|View full text |Cite
|
Sign up to set email alerts
|

GDM-Induced Macrosomia Is Reversed by Cav-1 via AMPK-Mediated Fatty Acid Transport and GLUT1-Mediated Glucose Transport in Placenta

Abstract: ObjectiveTo investigate if the role of Cav-1 in GDM-induced macrosomia is through regulating AMPK signaling pathway in placenta.MethodsWe used diagnostic criteria of gestational diabetes mellitus (GDM) and macrosomia to separate and compare placental protein and mRNA levels from GDM with macrosomia group (GDMM), GDM with normal birth weight group (GDMN) and normal glucose tolerance (NGT) with normal birth weight group (CON). Western blotting was performed to examine differentially expressed proteins of caveoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 31 publications
1
29
1
Order By: Relevance
“…AMPK activation is lower in the placenta from women with GDM [ 83 , 84 ]. This finding is complemented by high levels of TNF- α and activation of NF- κ B, conditions leading to increased synthesis of mediators of inflammation and impaired insulin action [ 85 , 86 ].…”
Section: Insulin Resistance In Pregnancy Diseasesmentioning
confidence: 99%
“…AMPK activation is lower in the placenta from women with GDM [ 83 , 84 ]. This finding is complemented by high levels of TNF- α and activation of NF- κ B, conditions leading to increased synthesis of mediators of inflammation and impaired insulin action [ 85 , 86 ].…”
Section: Insulin Resistance In Pregnancy Diseasesmentioning
confidence: 99%
“…PRKAA1 is important in glucose metabolism and energy homeostasis; it also interferes with the modulation of biological functions of cells ( 7 ). Previous studies have reported that PRKAA1 is aberrantly expressed in women with GDM and HG-treated vascular endothelial cells ( 8 , 9 ). Regarding potential upstream regulators of PRKAA1, microRNAs (miRNAs) are of interest in research.…”
Section: Introductionmentioning
confidence: 98%
“…The function of CAV1 in the placenta has not been fully elucidated, but it has been implicated in the transport of lipids, glucose homeostasis control, regulation of cell signalling, and membrane trafficking [65][66][67][68][69][70]. CAV1 is also involved in the palmitoylation of ERα, securing it to caveolae/lipid rafts on the cell membrane [71][72][73][74]. During pregnancy, CAV1 has been associated with glucose and fatty acid transport in the placenta by inducing AMPK and reducing the GLUT1 signalling pathway and reversing macrosomia due to gestational diabetes (GD) [74].…”
Section: Discussionmentioning
confidence: 99%
“…CAV1 is also involved in the palmitoylation of ERα, securing it to caveolae/lipid rafts on the cell membrane [71][72][73][74]. During pregnancy, CAV1 has been associated with glucose and fatty acid transport in the placenta by inducing AMPK and reducing the GLUT1 signalling pathway and reversing macrosomia due to gestational diabetes (GD) [74]. Furthermore, CAV1 has been implicated in the mechanism of oedema in preeclampsia (PE) following hypoxia of trophoblasts through the HMGB1/TLR4/CAV-1 pathway [75].…”
Section: Discussionmentioning
confidence: 99%